Alteraciones neurológicas en pacientes con virus de inmunodeficiencia humana. Hospital Carlos Andrade Marín. Quito, 2019-2020. - Kerly Joceline, Albán Rodríguez (2021)
ABSTRACT Clinical diseases of the central nervous system (CNS) represent a significant degree of morbidity in a high percentage of patients infected with human immunodeficiency virus (H.I.V) It is reported that 40-70% of patients infected with this virus present neurological alterations throughout the disease, which leads to high mortality. General objective: To determine the prevalence of neurological disorders in patients with human immunodeficiency virus at the Carlos Andrade Marín Hospital, located in Quito during the 2019-2020 period. Material and methods: Through a descriptive, observational and retrospective cross-sectional study that belongs to a descriptive model. The population was made up of 776 patients, all of them with a diagnosis of HIV who attend the Carlos Andrade Marín Specialty Hospital for the emergency service and hospitalization section of the infectology service during the year 2019-2020. Results: The data obtained allowed to determine the main alterations of the central nervous system, with cerebral toxoplasmosis occurring to 23% of patients, followed by Cerebral Histoplasmosis with 25%; Cerebral cryptococcosis occurs in 18.6%: Bacterial meningitis occurs in 14.2% and M Tuberculosis meningitis 10.6%, the other pathologies found occur with frequency less than 10%. Key words: HIV Infections, AIDS-Related Opportunistic Infections, Toxoplasmosis, Cerebral, Meningitis, Cryptococcal Reviewed by: Lcda. Diana Chávez English Professor. c.c. 065003795-5